Innovation in The Field of Education Personnel: Impact of Government Appointment Policies with Work Agreement (PPPK) on Employee Performance Case Study at MAN 1 Bekasi - Fathuloh, Fathuloh; Junaedi, Dedi; Sa’diyah, Titin; Zumaillah, Eli; Zaqiah, Qiqi Yuliati; Sopian, Sopian (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
The authors conducted this study aiming to reveal the impact of appointing Government Employees with Employment Agreements (PPPK) on employee performance at Madrasah Aliyah Negeri 1 Bekasi. The method used in this research is a descriptive qualitative method with data collection techniques used are observation and interviews. Interviews were conducted with Government Employees with Employment Agreements (PPPK), school principals, and heads of administrative staff and educators at the educational institution where the research was conducted. The results of the research were carried out through eight aspects of the performance of teaching staff; educate, teach, guide, direct, train, assess, evaluate, and the ability to innovate factors. Overall, all of these aspects show good performance, but the ability to innovate is still categorized as quite low.